Understanding the Preparation of Guidance and Counseling Programs - Bakhrudin All Habsy; Butsaina Altaf Atsila; Qonita Salsabila; Lino Fitriano; Shella Melati (Syntax Idea)
The development of guidance and counseling program is a complex process tha requires systematic planning. This study aims to examine the process of developing gudance and counseling program trough a literature rivew approach. The research employs a qualitative method with a literature rivew design. A literature review is a research method conducted by collecting, reviewing, and analyzing existing information from various relevant sources such as scientific journals, books, articles, and previous research reports. The result of this study Include the following: (1) Components of guidance and couseling programs, (2) Types of gudance and counseling programs, (3) Factors to consider in developing gudance and counseling programs, (4) requirements for developing guidance and counseling programs, (5) Stages of developing gudance and counseling programs, and (6) The structure of the gudance and counseling service implementation plan.